Food habits and nutritional status assessment of adolescent soccer players. A necessary and accurate approach - Iglesias-Gutierrez, E.; Garcia-Roves, P. M.; Rodriguez, C.; Braga, S.; Garcia-Zapico, P.; Patterson, A. M. (Canadian Journal of Applied Physiology, 2005)
The aim of this study was to assess the food habits and nutritional status of high level adolescent soccer players (N = 33; ages 14-16 yrs) living in their home environment. Body composition (height, mass, skinfolds), biochemical and hematological parameters, performance in soccer-specific tests (sprinting, jumping, intermittent endurance), and dietary intake (weighed food intake method) and related behaviors (nutrient supplement use, daily activity profile) were assessed. Daily energy expenditure and energy intake were 12.5 MJ and 12.6 MJ, respectively. Protein (16% of energy intake; 1.9 g/kg of body mass), lipid (38%), and cholesterol (385 mg) intake were above recommendations, while carbohydrates (45%) were below. The food intake of these adolescents was based on cereals and derivates; meat, fish, and eggs; milk and dairy products; biscuits and confectionery; and oil, butter and margarine, which provided 78% of total energy intake, 85% of proteins, 64% of carbohydrates, 90% of lipids, and 47% of fiber. Although diet provided sufficient iron, 48% of individuals showed iron deficiency without anemia. Based on these results, a well designed nutrition intervention would be advisable for optimizing performance, and especially for promoting healthy eating habits in adolescent soccer players.